Investigation and prosecution under the customs act 1967 / Zahari Ab. Wahab - Ab. Nahab, Zahari (Faculty of Law, 1985)
However courageous the Custom Officers are in fulfilling their duty, it would render futile with lack of knowledge on their legal Powers and limitations. In this computer age Custom Officers had to be more alert as rapid industrialisation creates complex cases not forseen by the author of the Act. It has to be remembered that smugglers are always one step forward than the custom officers but let's not hope the gap grows wide: With complex technologies. Custom Officers shouldering the burden of ensuring no loss to Government revenue by practise of unscrupulous businessman has to know off-hand his powers when acting against these irresponsible Criminals who design ways and means to evade or pay less taxes. This project paper seeks to examine with the guidance of case-laws the powers of custom officers in the course of investigation and Attempt to provide guideline to prosecuting officers.